Nifedipine Pharmacokinetics Are Influenced by CYP3A5 Genotype When Used as a Preterm Labor Tocolytic - Haas, David M.; Quinney, Sara K.; Clay, Jayanti M.; Renbarger, Jamie L.; Hebert, Mary F.; Clark, Shannon; Umans, Jason G.; Caritis, Steve N.; null (American Journal of Perinatology, 2013)
Objective To characterize the pharmacokinetics and pharmacogenetics of nifedipine in pregnancy.Study Design Pregnant women receiving oral nifedipine underwent steady-state pharmacokinetic testing over one dosing interval. DNA was obtained and genotyped for cytochrome P450 (CYP) 3A5 and CYP3A4*1B. Nifedipine and oxidized nifedipine concentrations were measured in plasma, and pharmacokinetic parameters were compared between those women who expressed a CYP3A5*1 allele and those who expressed only variant CYP3A5 alleles (*3,*6, or *7).Results Fourteen women had complete data to analyze. Four women (29%) expressed variant CYP3A5; three of these women were also CYP3A4*1B allele carriers. The mean half-life of nifedipine was 1.68 ± 1.56 hours. The area under the curve from 0 to 6 hours for the women receiving nifedipine every 6 hours was 207 ± 138 µg·h /L. Oral clearance was different between high expressers and low expressers (232.0 ± 37.8 µg/mL versus 85.6 ± 45.0 µg/mL, respectively; p = 0.007).Conclusion CYP3A5 genotype influences the oral clearance of nifedipine in pregnant women.
Keywords: nifedipine; pharmacokinetics; pharmacogenetics; pregnancy; tocolysis